Case Report: Non traumatic Cerebellar Hemorrhage in a Young Man - Perdawd, Khawand Saeed (International Journal of Health Sciences, 2023)
Intracerebral hemorrhage (ICH) is a seldom-seen event, occurring in around 10% of cases within the cerebellum. These incidents are more common among older adults and are frequently linked to hypertension. However, instances have also been documented in younger individuals, particularly those with arteriovenous malformations and angiomas. The occurrence of spontaneous cerebellar hemorrhages, unrelated to trauma or known risk factors, is exceptionally rare and has a mortality rate ranging from 25% to 57%. This case involved a 29-year-old male who experienced a spontaneous cerebellar hemorrhage. Despite being a healthy young adult without common risk factors for cerebrovascular accidents (CVAs), even not smoking.